DETERMINAN KEPUTUSAN PEMBELIAN PRODUK DI MINIMARKET: STUDI PADA KONSUMEN INDOMARET DI KUDUS - Anindita Evelyn Jessica Putri; Audrey Jennifer Octavatiya (Universitas YPPI Rembang, 2023)
ABSTRACTThe following study aims to analyze the effect of Halal Certification, Halal Awareness and Product Composition on Purchasing Decisions in minimarkets. With the predicted increase in consumption of halal products in Indonesia, consumers need to pay attention on several factors before deciding to buy products. The existence of halal certification makes the product more convincing to buy. The high awareness of halal consumers helps in the purchase decision process, and the inclusion of product composition makes consumers not hesitate to buy it. This study used Structural Equation Modeling (SEM) analysis with AMOS26 software. The following study used purposive sampling, which is based on criteria determined by researchers to obtain samples in non-probability sampling techniques and obtained 125 respondents. This study done by distributed questionnaires that were assessed by likert scale measurements. The results are Halal Certification did not affect the Purchasing Decision, while Halal Awareness and Product Ingredients has a significant positive effect on the Purchasing Decision. Consumers should pay more attention to halal certification on products, have good halal awareness and still pay attention to the composition of the product on the packaging before deciding to buy. Keywords: Halal Certification, Halal Awareness, Product Ingredients, Purchasing Decision, Structural Equation Modelling (SEM) AMOS. ABSTRAKPenelitian berikut bertujuan untuk menganalisis pengaruh Sertifikasi Halal, Kesadaran Halal dan Komposisi Produk terhadap Keputusan Pembelian produk di minimarket. Dengan adanya prediksi kenaikan konsumsi produk halal di Indonesia, konsumen perlu memerhatikan beberapa faktor sebelum memutuskan untuk membeli produk. Adanya sertifikasi halal membuat produk lebih meyakinkan untuk dibeli. Tingginya kesadaran halal konsumen membantu dalam proses keputusan pembelian, serta tercantumnya komposisi produk membuat konsumen tidak ragu untuk membelinya. Penelitian ini menggunakan analisis Structural Equation Modelling (SEM) dengan software AMOS26. Penelitian berikut menggunakan purposive sampling, yakni berdasarkan kriteria yang telah ditentukan oleh peneliti untuk mendapatkan sampel dalam teknik non-probability sampling dan diperoleh 125 responden. Peneliti melakukan penyebaran kuesioner yang dinilai dengan pengukuran skala likert. Hasil penelitian menunjukkan Sertifikasi Halal tidak berpengaruh terhadap Keputusan Pembelian, sedangkan Kesadaran Halal dan Komposisi Produk berpengaruh positif signifikan terhadap Keputusan Pembelian. Konsumen hendaknya lebih memerhatikan sertifikasi halal pada produk, memiliki kesadaran halal yang baik serta tetap memerhatikan komposisi produk pada kemasan sebelum memutuskan untuk membeli. Kata kunci: Sertifikasi Halal, Kesadaran Halal, Komposisi Produk, Keputusan Pembelian, Structural Equation Modelling (SEM) AMOS.